Impact of Sociodemographic Factors on the Early Initiation of Complementary Feeding in Padang City, Indonesia - Hermalinda Herman; Deswita; Ira Mulya Sari; Arif Rohman Mansur (Caring: Indonesian Journal of Nursing Science, 2025)
The World Health Organization (WHO) recommends introducing complementary foods at six months of age, while continuing breastfeeding up to two years or beyond. However, early or delayed initiation remains common, contributing to nutritional problems in developing countries. This study aimed to assess the prevalence of timely initiation of complementary feeding (CF) and identify sociodemographic factors associated with early introduction of complementary feeding among mothers of infants aged 6-23 months in Padang, Indonesia. A cross-sectional study was conducted among 244 mothers of infants aged 6–24 months. Data were collected using structured questionnaires covering sociodemographic characteristics and the time for introduction ofcomplementary feeding. Statistical analysis was performed using SPSS version 25, descriptive statistics described the prevalence of timely initiation, bivariate logistic regression assessed the relationship between sociodemographic factors and early initiation of CF. Most mothers (89.8%) initiated complementary feeding at the recommended age of 6–8 months, 9.0% introduced foods before six months, and 1.2% after eight months. Early initiation was significantly associated with maternal education level (p = 0.006), and grandmothers as source information (p = 0.010), where mothers with lower education were more likely to introduce foods prematurely (AOR = 3.39, 95% CI: 1.02–11.32). Mothers who received information from grandmothers were more likely to introduce CF on time (AOR = 2.73, 95% CI: 1.06–6.98). The study highlights the importance of education and family influence on infant feeding practices and recommends strengthening health education for mothers, especially those with lower education, to improve adherence to CF guidelines. Keyword: Early weaning, Complementary feeding, Maternal educational status, Socioeconomic factors, Grandparents